An Investigation of Creep Resistance in Grade 91 Steel through Computational Thermodynamics. (June 2020) - Smith, Andrew; Asadikiya, Mohammad; Yang, Mei; Chen, Jiuhua; Zhong, Yu
Abstract: This study was conducted to understand the relationship between various critical temperatures and the stability of the secondary phases inside the heat-affected-zone (HAZ) of welded Grade 91 (Gr.91) steel parts. Type IV cracking has been observed in the HAZ, and it is widely accepted that the stabilities of the secondary phases in Gr.91 steel are critical to the creep resistance, which is related to the crack failure of this steel. In this work, the stabilities of the secondary phases, including those of the M23 C6, MX, and Z phases, were simulated by computational thermodynamics. Equilibrium cooling and Scheil simulations were carried out in order to understand the phase stability in welded Gr.91 steel. The effect of four critical temperatures—that is, Ac1 (the threshold temperature at which austenite begins to form), Ac3 (the threshold temperature at which ferrite is fully transformed into austenite), and the M23 C6 and Z phase threshold temperatures—on the thickness of the HAZ and phase stability in the HAZ is discussed. Overall, the simulations presented in this paper explain the mechanisms that can affect the creep resistance of Gr.91 steel, and can offer a possible solution to the problem of how to increase creep resistance at elevated temperatures by optimizing the steel composition, welding, and heat treatment process parameters. The simulation results from this work provide guidance for future alloy development to improve creep resistance in order to prevent type IV cracking.